2017
DOI: 10.1111/phpp.12354
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of sunburn among beachgoers

Abstract: It is necessary to develop photoprotection campaigns aimed at beachgoers, particularly in young people, men, those with skin phototypes I-III and secondary or university education. Educational strategies should be aimed at discouraging sun exposure at midday, changing attitudes towards tanning and improving knowledge about skin cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
1
12
2
Order By: Relevance
“…We found that more than 60% had suffered at least one sunburn in the last summer, a percentage higher than those reported in studies conducted in the US (Buller et al, 2011; Holman et al, 2014) and Europe (De Troya-Martín et al, 2018; Haluza et al, 2016; Kritsotakis et al, 2016). This may be due to the lack of education in the local population, which negatively affects their practices and habits regarding sun exposure.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…We found that more than 60% had suffered at least one sunburn in the last summer, a percentage higher than those reported in studies conducted in the US (Buller et al, 2011; Holman et al, 2014) and Europe (De Troya-Martín et al, 2018; Haluza et al, 2016; Kritsotakis et al, 2016). This may be due to the lack of education in the local population, which negatively affects their practices and habits regarding sun exposure.…”
Section: Discussioncontrasting
confidence: 73%
“…This may be linked to the attitudes that, according to our study, were also better in women. In addition, this could explain why sunburns are more frequent in men, according to some studies (De Troya-Martín et al, 2018; Reuter et al, 2010; Kasparian, McLoone & Meiser, 2009).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations